Understanding of reservoir gas compositions in a natural case using stepwise semi-open artificial maturation - Michels, Raymond; Enjelvin-Raoult, Noële; Elie, Marcel; Mansuy, Laurence; Faure, Pierre; Oudin, Jean-Louis (Marine and petroleum geology, 2002)
In a study of the gas distribution and composition in different reservoirs of multilayered gas fields in South-East Asia, two types of variations with depth of the δ 13C values of gases (in particularly methane) were observed. In the normally pressured zones, the δ 13C values of methane increase steadily with depth, whilst in some overpressured zones, they first decrease with depth and then follow a regular trend. In order to explain these patterns, these data were compared to those obtained by artificial maturation of a coal using confined pyrolysis. Experiments were conducted in perfectly closed and in semi-open conditions. The free gases recovered were quantified by gas chromatography and the carbon isotopic composition of individual compounds (C 1–C 5 hydrocarbons) determined. The evolution of the δ 13C versus pyrolysis temperature obtained for the artificially generated methane is very similar to that of the natural gas. The use of the δ 13C 2– δ 13C 3 versus C 2/C 3 mol% diagram [EAGE 58th Conference and Technology Exhibition, 1996; Chem. Geol. 147 (1998) 249] allows recognition of two trends in the artificial maturation data related to the degree of opening of the experimental systems. Comparison of the data provide evidence that the closed pyrolysis results are very similar to those observed in high pressured reservoirs while those obtained in the normal pressured reservoirs follow the values of semi-open pyrolysis. The gas distributions and carbon isotope composition in the reservoirs can therefore be explained in terms of degree of opening of the system: high pressure reservoirs can be considered as fairly closed systems, with in situ gas generation, while normally pressured zones are more open and subject to important lateral migration. The composition of the gas (richness in methane) is controlled by the degree of opening of the system. Thus, our findings do not support the hypothesis that the generation of methane-rich gases in nature is controlled by transition metal catalysis.